Biochemistry and transcriptome analysis reveal condensed tannins alleviate liver injury induced by regulating cholesterol metabolism pathway - Xiangxin Li; Yijing Pu; Bangdi Liu; Xiaoming Fang; Wenjun Peng; Weibo Jiang; Wenli Tian (Food Science and Human Wellness)
Free cholesterol has been considered to be a critical risk factor of nonalcoholic fatty liver disease (NAFLD). It remains unknown whether dietary intake of condensed tannins (CTs) have distinguishable effects to alleviate liver damage caused by a high cholesterol diet. Male C57BL/6 mice were fed a high cholesterol diet for 6 weeks, and given CTs treatment at a dosage of 200 mg/(kg·day) at the same time. The results indicated that compared with mice fed a normal diet, a high cholesterol diet group resulted in significant weight loss, dysregulation of lipid metabolism in blood and liver, and oxidative stress in the liver, but CTs treatment dramatically reversed these negative effects. Hematoxylin and eosin (H&E) staining and frozen section observation manifested that CTs treatment could effectively reduce the deposition of liver cholesterol and tissue necrosis caused by high cholesterol intake. CTs alleviated liver injury mainly by regulating the expression of related genes in cholesterol metabolism pathway and AMPK phosphorylation. Our results confirmed that CTs have remarkable cholesterol lowering and anti-liver injury effects in vivo.